2020
DOI: 10.1021/acsbiomaterials.9b01844
|View full text |Cite
|
Sign up to set email alerts
|

Hypericin-Loaded Transferrin Nanoparticles Induce PP2A-Regulated BMI1 Degradation in Colorectal Cancer-Specific Chemo-Photodynamic Therapy

Abstract: Epigenetically regulated therapeutic intervention of cancer is an emerging era of research in the development of a promising therapy. Epigenetic changes are intrinsically reversible and providing the driving force to drug resistance in colorectal cancer (CRC). The regulation of polycomb group (PcG) proteins, BMI1 and EZH2, and the associated CRC progression hold promises for a novel treatment regime. The present study enlightens targeted photodynamic therapy (PDT) with potential photosensitizer hypericin nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…92 Whereas, studies by Sardoiwala et al (2020) synthesized a hypericin-loaded transferrin nanoformulation (HTfNPs) composite, to overcome the PSs hydrophobicity and poor bioavailability, as well as serve as a PDT epigenetic-based CRC therapy. 93 This transferrin targeted PDT signicantly induced BMI1 degradation assisted CRC in vitro cell retardation, as well as improved hypericin's availability at diseased sites. 93 However, concerningly studies by Kaleta-Richter et al (2020) noted that hypericin-mediated PDT, stimulates release of interleukin-8 and -10 in CRC, which is responsible for the progression of cancer and metastasis.…”
Section: Photosensitizers For Pdd and Pdt Colorectal Cancer Applicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…92 Whereas, studies by Sardoiwala et al (2020) synthesized a hypericin-loaded transferrin nanoformulation (HTfNPs) composite, to overcome the PSs hydrophobicity and poor bioavailability, as well as serve as a PDT epigenetic-based CRC therapy. 93 This transferrin targeted PDT signicantly induced BMI1 degradation assisted CRC in vitro cell retardation, as well as improved hypericin's availability at diseased sites. 93 However, concerningly studies by Kaleta-Richter et al (2020) noted that hypericin-mediated PDT, stimulates release of interleukin-8 and -10 in CRC, which is responsible for the progression of cancer and metastasis.…”
Section: Photosensitizers For Pdd and Pdt Colorectal Cancer Applicationsmentioning
confidence: 95%
“…93 This transferrin targeted PDT signicantly induced BMI1 degradation assisted CRC in vitro cell retardation, as well as improved hypericin's availability at diseased sites. 93 However, concerningly studies by Kaleta-Richter et al (2020) noted that hypericin-mediated PDT, stimulates release of interleukin-8 and -10 in CRC, which is responsible for the progression of cancer and metastasis. 74 Thus, PDT applications with third-generation hypericin PS, seems rather controversial and no studies noting its application in effective CRC PDD were found.…”
Section: Photosensitizers For Pdd and Pdt Colorectal Cancer Applicationsmentioning
confidence: 95%
“…Some of the widely investigated receptors and possible targets for CRC PDT include the epidermal growth factor receptor (EGFR), transferrin receptors, fibroblast growth factor receptors (FGFR), and the epithelial cell-adhesion molecule (EpCAM), among others [13]. For example, the transferrin receptor (CD71) is generally expressed to regulate iron homeostasis within normal human cells, however, malignant tumours are often found to express abnormal levels of expression of the transferrin receptor (CD71), which may be targeted by antibodies in targeted PDT [92]. In one study, Sardoiwala et al [92] synthesised hypericin-loaded transferrin nanoformulations (HTfNPs) for the treatment of colorectal cancer [92].…”
Section: Active Targeting Strategymentioning
confidence: 99%
“…Iron is vital for cell proliferation, and due to the increased need of tumors for nutrients, including iron, the overexpression of TFR1 is identified in cancer patients including CRC [ 94 , 95 ]. While the abundance of TFR1 impacts colorectal cancer cell proliferation rates [ 96 ], this is particularity appealing for engineering nanoparticles in CRC-targeted therapy by surface functionalization with TFR’s natural ligand transferrin [ 97 , 98 , 99 , 100 ].…”
Section: Targeting Strategies For Drug-delivery Systems In Crcmentioning
confidence: 99%